Shear bond strength of three different fixed retainers: Stainless steel wires versus fiber reinforced composite (An in Vitro study) - Anees Mahmood Mudhir (Erbil Dental Journal)
Background and Objectives: Long term preservation of lingual retainer after active orthodontic treatment is mandatory in oral cavity to prevent teeth relapse to its original place before treatment which is documented in orthodontics and considered as a success factor of lingual bonded retainers. This in vitro study is conducted to evaluate and compare the bond strength (shear bond strength) of three different fixed lingual retainers using a specific retainer composite and fracture modes of different retainer’s wire/adhesive combination.